Advancements in targeted and immunotherapy strategies for glioma: toward precision treatment - Guangyuan Gong; Lang Jiang; Jing Zhou; Yuanchao Su (Frontiers in Immunology)
In recent years, significant breakthroughs have been made in cancer therapy, particularly with the development of molecular targeted therapies and immunotherapies, owing to advances in tumor molecular biology and molecular immunology. High-grade gliomas (HGGs), characterized by their high malignancy, remain challenging to treat despite standard treatment regimens, including surgery, radiotherapy, chemotherapy, and tumor treating fields (TTF). These therapies provide limited efficacy, highlighting the need for novel treatment strategies. Molecular targeted therapies and immunotherapy have emerged as promising avenues for improving treatment outcomes in high-grade gliomas. This review explores the current status and recent advancements in targeted and immunotherapeutic approaches for high-grade gliomas.